Method for Predicting the Outcome of Burn Injury Based on a Mathematical Model - E. A. Zhirkova; T. G. Spiridonova; O. G. Sinyakova; A. V. Sachkov; A. O. Medvedev; E. I. Eliseenkova; I. G. Borisov; M. L. Rogal; S. S. Petrikov (Неотложная медицинская помощь)
The choice of treatment tactics for a patient with burns should be based on individual prediction of injury outcome. Known models for predicting the outcome of burn injury are inaccurate and do not allow us to determine the probability of different outcomes for a particular patient.AIM OF THE STUDY. To develop a method for individual prediction of the outcome of burn injury based on a mathematical model using the revised Frank index.MATERIAL AND METHODS. 399 patients: men 283 (71%), women 116 (29%); age — 50 (36; 66) years; total burn area — 25 (15; 40) % TBSA, I–II degree — 20 (10; 30) % TBSA, III degree — 8 (3; 20) % TBSA. In 140 (35%) patients, inhalation injury was detected.Based on the number of revised Frank Index (RFI) scores (in increments of 10), frequency diagrams of different outcomes were constructed. The mathematical model of individual prognosis is based on a regression equation that was derived from an approximated curve of the proportions of a favorable outcome in the optimal RFI range.RESULTS. Patient survival probability (%) depending on the number of RFI points was distributed as follows: with RFI<72 — ≥99.9%; for RFI ≥72 ≤189, the probability of survival is calculated using the formula obtained as a result of approximation by a 4th degree polynomial of the curve of the dependence of survival on the number of RFI points: 0.0049x4 – 0.1027x3 – 0.1624x2 + 2.6794x + 96.54 ; where x= (RFI -35)/10; with RFI>189 — ≤0.1%. The probability of a lethal outcome is determined by subtracting the resulting probability of a survival from 100%.CONCLUSION. The developed method for predicting the outcomes of a burn injury based on a mathematical model allows us to determine the probability of different outcomes for a particular patient.